Shock Waves 26th International Symposium on Shock Waves, Volume 2 - Hannemann, Klaus; Seiler, Friedrich (Springer Berlin Heidelberg : Imprint: Springer, 2009)
The 26th International Symposium on Shock Waves in Göttingen, Germany was jointly organised by the German Aerospace Center DLR and the French-German Research Institute of Saint Louis ISL. The year 2007 marked the 50th anniversary of the Symposium, which first took place in 1957 in Boston and has since become an internationally acclaimed series of meetings for the wider Shock Wave Community. The ISSW26 focused on the following areas: Shock Propagation and Reflection, Detonation and Combustion, Hypersonic Flow, Shock Boundary Layer Interaction, Numerical Methods, Medical, Biological and Industrial Applications, Richtmyer Meshkov Instability, Blast Waves, Chemically Reacting Flows, Diagnostics, Facilities, Flow Visualisation, Ignition, Impact and Compaction, Multiphase Flow, Nozzle Flows, Plasmas and Propulsion. The two volumes contain the papers presented at the symposium and serve as a reference for the participants of the ISSW 26 and individuals interested in these fields.